Whitefly feeding behavior and retention of a foregut‐borne crinivirus exposed to artificial diets with different pH values. (16th August 2017) - Zhou, Jaclyn S.; Chen, Angel Y. S.; Drucker, Martin; Lopez, Nicole H.; Carpenter, Alyssa; Ng, James C. K.
Abstract: Transmission of plant viruses by phytophagous hemipteran insects encompasses complex interactions underlying a continuum of processes involved in virus acquisition, retention and inoculation combined with vector feeding behavior. Here, we investigated the effects of dietary pH on whitefly ( Bemisia tabaci ) feeding behavior and release of Lettuce infectious yellows virus (LIYV) virions retained in the vector's foregut. Electrical penetration graph analysis revealed that variables associated with whitefly probing and ingestion did not differ significantly in pH (4, 7.4, and 9) adjusted artificial diets. To investigate virus retention and release, whiteflies allowed to acquire LIYV virions in a pH 7.4 artificial diet were fed pH 4, 7.4, or 9 virion‐free artificial (clearing) diets. Immunofluorescent localization analyses indicated that virions remained bound to the foreguts of approximately 20%–24% of vectors after they fed on each of the 3 pH‐adjusted clearing diets. When RNA preparations from the clearing diets were analyzed by reverse transcription (RT) nested‐PCR and, in some cases, real‐time qPCR, successful amplification of LIYV‐specific sequence was infrequent but consistently repeatable for the pH 7.4 diet but never observed for the pH 4 and 9 diets, suggesting a weak pH‐dependent effect for virion release. Viruliferous vectors that fed on each of the 3 pH‐adjusted clearing diets transmitted LIYV to virus‐free plants. These results suggest that changes in pH values alone in artificial diet do not result in observable changes in whitefly feeding behaviors, an observation that marks a first in the feeding of artificial diet by whitefly vectors; and that there is a potential causal and contingent relationship between the pH in artificial diet and the release/inoculation of foregut bound virions.